PERAN FRAUD TRIANGLE TERHADAP KECURANGAN LAPORAN KEUANGAN - Gading, Audi Elshinta; Handayani, Sebrina; Sitepu, Ariyanta Maulana; Simanjorang, Morina; Supraja, Galih (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The purpose of this study is to comprehensively understand and examine how the Fraud Triangle contributes to financial statement fraud. This study employs a descriptive literature review strategy. Six out of nine analyzed publications indicate that the Fraud Triangle has a significant impact on financial statement fraud. Quantitative data studies support this conclusion by demonstrating a strong positive relationship between the discussed fraud and the components of the Fraud Triangle. On the other hand, according to three other studies, financial statement fraud is not significantly influenced by the Fraud Triangle. This phenomenon reflects that, despite many companies implementing internal control systems, weaknesses in their execution still allow fraud to occur.